2013
DOI: 10.12691/ajme-1-5-6
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Intake Port of Diesel Engine for Target Value of Swirl

Abstract: The mutual desire for higher fuel economy and greater performance along with stringent emission regulations set by the government for diesel engines necessitates enhanced air-fuel mixing for proper combustion. The design of intake port plays a major role in an engine design, development and optimization, as it controls the power developed, fuel consumed and exhaust emissions from the engine. The effects of different geometrical parameters of helical port on swirl performance were studied. A methodology is prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In previous research data, it was said that installing swirl generator increases the swirl performance but decreases the volumetric efficiency. 4,[19][20][21] HSSIV proposed in this study is considered to be an effective method to increase the mixing performance of air and fuel and to increase combustion efficiency by increasing the swirl ratio and TKE without having a negative effect on the volumetric efficiency from its geometrical characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research data, it was said that installing swirl generator increases the swirl performance but decreases the volumetric efficiency. 4,[19][20][21] HSSIV proposed in this study is considered to be an effective method to increase the mixing performance of air and fuel and to increase combustion efficiency by increasing the swirl ratio and TKE without having a negative effect on the volumetric efficiency from its geometrical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that as the valve shroud angle increased, the swirl increased and conversely the volumetric efficiency decreased. Sabale and Sanap 20 studied the influence of the helical inlet port design parameters (dimensions and angles) on the swirl generation.…”
Section: Introductionmentioning
confidence: 99%
“…The most important function of Diesel engine combustion chamber is to provide proper air and fuel mixture in short span of time. In order to get this, an proper air movement named as swirl is provided to generate high relative velocity between the air and fuel droplet [1]. During the air jet is injected into the combustion chamber, the spray cone getting disturbed due to air motion inside that can be guided by the intake port, makes it necessary to study the helical port design in detail.…”
Section: Introductionmentioning
confidence: 99%
“…S.K Sabaleand S.B. Sanab [4] has developed a methodology for design of helical inlet port targeting high swirl number of the order of 1.8 and experimentally tested in paddle wheel facility.…”
Section: Introductionmentioning
confidence: 99%